Convergent Synthesis of Branched β-Glucan Tridecasaccharides Ready for Conjugation - Zhou, Xin; Long, Qing; Li, Dongwei; Gao, Jingru; Sun, Qikai; Sun, Shaozi; Su, Yong; Wang, Peng; Peng, Wenjie; Li, Ming (Synthesis, 2021)
Structurally defined and pure oligosaccharides corresponding to β-glucans have attracted great attention because of their potential properties as immunostimulating agents and as antigens of vaccine candidates. We herein describe a convergent synthesis of ready-to-conjugate tridecasaccharides composed of a β-1,3-glucan nonasaccharide backbone and a β-1,6-glucan tetrasaccharide branch. The assembly was achieved by employing trichloroacetimidate glycosylations and features the gram-scale preparation of the nonasaccharide backbone and installation of the tetrasaccharide branch involving orthoester rearrangement to the glycoside.
Keywords: β-glucans; glycosyl trichloroacetimidates; oligosaccharide synthesis; orthoester rearrangement; convergent synthesis